Game Design to Introduce Pets - Wahyu Febriyanto; Brenda Chandrawati; Erdhi Widyarto (Soegijapranata Catholic University, 2016)
Introduction of animals from an early age can make children to love animals, especially pets. Children are the easiest group to receive stimulation, such as for example the stimulation of introducing children to the pet. Various media are used by parents to introduce pet. For examplle, by the media of books, multimedia, etc. One of the interesting media to introduce pet is with game. Of these problems then need to know how to make concept and design game to introduced pets for children age 3-6 years. In this paper, author formulate how to make pet game design include game genre, user interface design, image model selection, game characters, and game engine. The expected design of this game can be formulation of learning through proper game as a learning tool children. Game design derived from this writing by using model 2-dimensional images are funny and interesting coloring. And combines several game genres into one, or use the mini games that children do not get bored quickly. Design of GUI (Graphical User Interface) is made as simple as possible so that children easily understand in playing this game, but also must use an interesting image